Psychological Approach to Smoking Relapse Prevention : A Systematic Review - Miskah Afriani; Yuzana Binti Mohd. Yusop; Harmy Bin Muhamed Yusof (Pena Cendekia Insani, 2022)
Background: An estimated that the number of smokers reaches 1.3 billion daily smokers worldwide. Some countries show a high prevalence of cigarette consumption among men, such as Russia 59.0%, Ukraine 49.4%, Morocco 45.4%, China 47.6%, Indonesia 76.2%, and Pakistan 41.9%. Thus, Asian countries such as Indonesia consume more cigarettes than Western countries. In the Western countries, there are some countries with the highest mortality rates caused by smoking for instance the United States of 492,400 annual mortality rates, and another one is Russia with more than 309,500 annual mortality rates. The next country in the Asia region with the highest annual mortality rate led by Indonesia, which is more than 225,700 annual mortality rates, then China has more than 195,200 annual mortality rates. One of the efforts to stop smoking is to conduct behavioral/psychological approaches such as counseling. Counseling or therapy can increase the tendency to stop smoking compared to not doing counseling. Objectives: to provide comprehensive information about psychological approaches to relapse prevention such as CBT, hypnosis therapy, positive psychology, individual counseling and group therapy. Result: this study found 18 literature that discussed psychological approaches is evidenced to relapse prevention about 20-45% single or multi counseling and additional pharmacological treatment. Behavioral approaches such as counseling can increase the tendency to relapse prevention compared to not doing counseling and the combination of two behavioral treatments in one intervention will produce higher effectiveness, such as CBT plus telephone counselling